2012
DOI: 10.1007/s10265-012-0525-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of auxin physiological analogues on rapeseed (Brassica napus) cold hardening, seed yield and quality

Abstract: The effect of the auxin physiological analogues analogues 1-[2-chloroethoxycarbonylmethyl]-4-naphthalenesulfonic acid calcium salt (TA-12) and 1-[2-dimethylaminoethoxicarbonylmethyl]naphthalene chlormethylate (TA-14) TA-14 on different winter rapeseed cultivars were studied with regard to their autumnal growth, cold hardening, accumulation of the stress-protective metabolites proline and saccharide in plant organs: apical bud and root collum, winter survival and productivity formation. The test cultivars were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…In Arabidopsis and Rice, a significant number of auxin-regulated genes are additionally affected by cold stress [44,49]. When auxin analogs were applied on Brassica napus , it stimulated the accumulation of freeze-protective metabolites and soluble sugars during cold hardening [50]. Therefore, we speculated that auxin might play an important role in Brassica napus response to freezing stress.…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis and Rice, a significant number of auxin-regulated genes are additionally affected by cold stress [44,49]. When auxin analogs were applied on Brassica napus , it stimulated the accumulation of freeze-protective metabolites and soluble sugars during cold hardening [50]. Therefore, we speculated that auxin might play an important role in Brassica napus response to freezing stress.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, it was shown that after treatment with the auxin-like compounds TA-12 and TA-14, the winter resistance of the studied oilseed rape cv. ‘Valesca’ increased [ 32 ]. In the current study, we extend knowledge about the integration of auxin-like compounds into cell systems during the preparation for wintering.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of the structure and activity of these auxin-like compounds has shown that the activity of the compounds TA-12 and TA-14 is determined by the two methylene groups in their molecules, as well as a sulfo group that is attached to the naphthalene ring (TA-12) and a methyl group (CH 3 ) that is attached to N + (TA-14). Our previous study showed the effect of auxin-like compounds on the accumulation of proline and saccharides in the root collar and terminal bud in oilseed rape and, furthermore, that these compounds influence the acclimation of plants to the cold, overwintering, and productivity formation [ 32 ]. However, from a theoretical point of view, these results also raised a question regarding which metabolic processes may also be integrated into the metabolism of the cell systems during the cold acclimation period, successfully overwintering, and maintaining dormancy in plants.…”
Section: Introductionmentioning
confidence: 99%
“…They contribute to the development of rootage [15] and nutrient absorption, increase photosynthetic activity and improve their ability to cope with environmental stress factors [16,17]. For example, application of artificial auxin analogues, increased the content of proline and saccharose of the roots and shoot tips of rape, which led to the survival of an increased number of overwintered plants and also improved their growth indicators [18].…”
Section: David Publishingmentioning
confidence: 99%